"Libanicoccus massiliensis" gen. nov., sp. nov., a new bacterium isolated from a stool sample from a pygmy woman. (January 2017) - Bilen, M.; Cadoret, F.; Fournier, P.-E.; Daoud, Z.; Raoult, D.
Abstract: This study supports the main characteristics of a new genus "Libanicoccus massiliensis" strain Marseille-P3237 (CSURP3237); a new member of the order Coribacteriaceae that was isolated from a stool sample from a healthy 35-year-old pygmy woman.